Preventing Fraud in Accounting and Methods Used: Forensic Case Examples and Analysis in Osmaniye Province - Önal, Servet; Kırış, Yunus (Atlas Journal, 2024)
This study contains information about the prevention of fraud in accounting and the methods used. Businesses are vulnerable to cheating due to their organizational structure and activities. For this reason, it is necessary to reveal accounting frauds and to reveal what the measures can be taken, and to distinguish whether the mistakes made in the accounting system are mistakes or frauds. Considering the increasing number and amount of transactions in our world where technology is rapidly developing in parallel with these developments, explanations about which methods can be used in order to prevent accounting fraud were analyzed, and results and recommendations were made by analyzing the judicial cases related to fraud in the province of Osmaniye.